Maturazione funzionale della corteccia: il fondamento della vitalità - Gatti, Maria Gabriella; Becucci, Elisa; Fargnoli, Francesco; Fagioli, Massimo; Ådén, Ulrika; Buonocore, Giuseppe (Il sogno della farfalla, 2012)
The term “viability” is not simply synonymous with being “born alive,” but is closely related to the capability of having a “meaningful life” and having a reasonable period of survival. The definition of “viability” is generally based on two major criteria: the biological, which takes into consideration the maturity of the foetus, and the epidemiological, which is based on the survival rates reported in literature. The neuromaturation of the cerebral cortex is a dynamic process promoted by the subplate, a transient population of neurons that guides the development of cortical and thalamocortical connections. These connections are for example fundamental for cortical processing of sensory information and mental processes. The first thalamocortical and cortico-cortical connections grow at 23-24 postconceptional weeks, which coincides with the age limit for premature baby survival.